Relações de gênero nos livros didáticos de Língua Inglesa e perspectiva de docentes da rede pública: reprodução ou superação de estereótipos? - LURYAN SILVA FERNANDEZ (2024)
This is a qualitative study and it aims to verify the visual and/or textual contents of English Language (EL) textbooks used in the final years of public education Corumbá-MS, which includes the 6th, 7th , 8th and 9th grades of Elementary School. The books separated for analysis belong to the Programa Nacional do Livro e do Material Didático (PNLD) 2020 (edited in 2018) of the English curricular component and It Fits collection. In view of this, we sought to identify from a post-structuralist perspective, whether the speeches present in this didactic collection contribute to breaking or reproducing socially constructed gender stereotypes and what is the view of English teachers from the public Corumba city education on the constructions of meaning related to the themes of gender and sexuality printed in these books with which they work in pedagogical practice. So that getting the objectives to be achieved, a theoretical survey was carried out in the Theses and Dissertations Database (BDTD) based on three descriptors that convey gender and sexuality studies and the English teaching in Brazil. For empirical research, two data collection instruments were used: document analysis and semi-structured interviews. The discussions of both, books and interviews, were systematized through the content analysis proposed by Bardin (2016) and the results are presented based on analytical categories from DA (Discursive Analysis) perspective. The categories listed after checking the textbooks are: 1. Types of family; 2. Leisure activities; 3. Holsehold chores; 4. Professions; 5. Men teachers in early education; 6. All kinds of diversity?. Likewise, the results of the interviews are subdivided into: 1. “Casa de vespeiro” – the fear surrounding gender relations and school; 2. “The book has to focus on didactical”; 3. “They are in the process of forming their thoughts”; 4. “Cultural. It’s something that comes from ingrained habits.” 5. “Is it a theme to be approached? It is. In any area.” The LD is considered a multimodal tool with discourses embedded in the representations of visual or written texts, which were selected and interpreted in this study, providing explicit or implicit themes in each volume of the didactic book It fits. It is understood that the collection tends to break gender stereotypes in some specific book’s approaches, such as the visual and textual presentation of family structures in the 6th book. However, under a general analysis, LDs strictly follow the Base Nacional Comum Curricular (BNCC), which excludes gender relations from all text and the English Language curricular component, which makes it difficult to approach the topic either in the books than to the teachers in their classes. Some of the teachers expressed their support for dealing with the topic of gender and sexuality in EL classes, reporting experiences, based on representations in LDs, in which it was possible to discuss respect for differences, gender equality and diversity. However, there was a fear in the english teachers’ speeches when dealing with the issue, as they fear reprisals from the school community.